Pengembangan Multimedia dan Video Pembelajaran sebagai Inovasi Pembelajaran Pendidikan Agama Islam - Shakilla Zerlindah Maulana; Ananda siti Nurpadilah; Teguh Maulana; Denissa Aulia Ramadhani (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research seeks to examine the progression of multimedia and educational videos as an advancement in Islamic Religious Education (PAI). The study employs a qualitative methodology utilizing a library research technique by gathering information from scholarly journals, books, and pertinent academic references. Techniques for gathering data involve reading, recognizing, and categorizing literature, whereas data analysis employs content analysis to achieve a thorough comprehension of the subject. The findings of this research suggest that multimedia and educational videos significantly enhance the quality of PAI education. Utilizing multimedia can foster a more interactive, captivating, and efficient learning atmosphere, thus enhancing students' enthusiasm and comprehension of educational content. Educational videos additionally facilitate the illustration of abstract religious ideas in a more tangible and contextual way. Nonetheless, the execution of multimedia learning still encounters various obstacles, including inadequate technological infrastructure, low digital skills among educators, and insufficient institutional backing. To address these challenges, strategic actions are essential, such as enhancing teacher skills, ensuring proper facilities, and incorporating multimedia with interactive learning techniques. Thus, the creation of multimedia and educational videos can act as a powerful innovation in improving the standard of Islamic Religious Education in the digital age. Keywords: Islamic Religious Education, Learning Innovation, Learning Video, Multimedia, Student Understanding